GIS-based urban village regional fire risk assessment and mapping - Hermawan, Yonathan Andri; Warlina, Lia; Mohd, Masnizah (Universitas Komputer Indonesia, 2021)
Fires in residential areas are one of the threats out of 13 disasters in Indonesia. Fires are disasters based on their causes, classified as disasters caused by human negligence. This research aims to identify residential fire incidents, assess fire risk levels, and map the risk level. We used the geographic information system (GIS) analysis approach and direct observation of the study area. The research location was in the Tamansari sub-district in Bandung City. The subdistrict of Tamansari consists of 20 neighborhood units (rukun warga/ RW) with 22,995 people and 6,598 households. We conducted a field survey from December 2019 to March 2020. We used a spatial approach to analyze fire risk in this residential area by using GIS to map urban-village regional fire incidents and assess the risk level. There were four fire hazard variables: population density, building density, building quality, road class. On the other hand, vulnerability variables are based on the community's social parameters: population density, percentage of old age and children under five, people with disabilities, and the population's sex ratio. The hazard and vulnerability maps overlay showed three neighborhood units (rukun warga/ RW) with a high risk of fire, eight RWs with a moderate risk of residential fires, and nine RWs with a low risk of residential fires. The areas with low-risk categories must remain vigilant because the width of the roads in these areas is relatively narrow.